Contemporary perspectives through action research across educational disciplines : the K-12 classroom - Nasr, Nancy T.; Perry, Jill Alexa (Contemporary perspectives through action research across educational disciplines, 2023)
"The mission of the Action Research Across Educational Disciplines series is to present targeted volumes of action research findings from a wide variety of educational settings. Specifically, this series aims to highlight the issues that commonly impact practitioners, counselors, administrators, and other stakeholders in education. The rationale for such a series comes from the continually evolving educational landscape, resulting from changing student demographics and societal needs. To face the contemporary issues that surface as a result of this changing educational landscape, educators must prepare for and lead through the change with an intent on overcoming these issues through improvements to their daily practice. As many educators are left without tools or resources to make a stronger impact in their educational contexts, this series will serve as a mentor text that provides examples of studies undertaken by practitioners using action research to improve their practice. As a result, Action Research Across Educational Disciplines will present the tools and findings associated with action research to educators across the broad field of K-12 education, and beyond, wishing to improve and transform their practice. This first volume of the Action Research Across Educational Disciplines series presents action research findings from a wide variety of K-12 disciplinary settings. In doing so, the first volume of this series aims to highlight the issues that commonly impact practitioners in K-12 STEM, English, Social Science, and even Art classrooms, and illustrate the solutions proposed in these contexts to improve both educator practice and student achievement. Through the use of action research methodologies to address such issues, volume one of this series offers a resource for improving educational practice across diverse K-12 contexts"--